The internal dose makes the poison: higher internalization of polystyrene particles induce increased perturbation of macrophages - Collin-Faure, Véronique; Vitipon, Marianne; Torres, Anaëlle; Tanyeres, Ornella; Dalzon, Bastien; Rabilloud, Thierry (Frontiers in Immunology, 2023)
Plastics are emerging pollutants of great concern. Macroplastics released in the environment degrade into microplastics and nanoplastics. Because of their small size, these micro and nano plastic particles can enter the food chain and contaminate humans with still unknown biological effects. Plastics being particulate pollutants, they are handled in the human body by scavenger cells such as macrophages, which are important players in the innate immune system. Using polystyrene as a model of micro and nanoplastics, with size ranging from under 100 nm to 4 microns, we have showed that although non toxic, polystyrene nano and microbeads alter the normal functioning of macrophages in a size and dose-dependent manner. Alterations in the oxidative stress, lysosomal and mitochondrial functions were detected, as well as changes in the expression of various surface markers involved in the immune response such as CD11a/b, CD18, CD86, PD-L1, or CD204. For each beads size tested, the alterations were more pronounced for the cell subpopulation that had internalized the highest number of beads. Across beads sizes, the alterations were more pronounced for beads in the supra-micron range than for beads in the sub-micron range. Overall, this means that internalization of high doses of polystyrene favors the emergence of subpopulations of macrophages with an altered phenotype, which may not only be less efficient in their functions but also alter the fine balance of the innate immune system